2021
DOI: 10.1101/2021.09.27.21264041
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing inertial measurement unit locations for freezing of gait detection and patient preference

Abstract: Background: Freezing of gait, a common symptom of Parkinson's disease, presents as sporadic episodes in which an individual's feet suddenly feel stuck to the ground. Inertial measurement units (IMUs) promise to enable at-home monitoring and personalization of therapy, but there is a lack of consensus on the number and location of IMUs for detecting freezing of gait. The purpose of this study was to assess IMU sets in the context of both freezing of gait detection performance and patient preference. Methods: Si… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Typically, inertial measurement units (IMUs) are placed on various limbs of subjects, including the feet, shanks, knees, etc., and their built-in accelerometers, gyroscopes, and magnetometers can record different features of PD movement. A recent study using IMUs coupled with convolutional neural network modeling to track FOG in PD subjects explored sensor locations that maximized patient adherence for personalized athome motor symptom monitoring (O Day et al, 2022). Additionally, smartphones can measure spatiotemporal features of rest tremor using a three-dimensional built-in accelerometer and robust software packages.…”
Section: Emerging Technologies In Assessing Motor Functionmentioning
confidence: 99%
“…Typically, inertial measurement units (IMUs) are placed on various limbs of subjects, including the feet, shanks, knees, etc., and their built-in accelerometers, gyroscopes, and magnetometers can record different features of PD movement. A recent study using IMUs coupled with convolutional neural network modeling to track FOG in PD subjects explored sensor locations that maximized patient adherence for personalized athome motor symptom monitoring (O Day et al, 2022). Additionally, smartphones can measure spatiotemporal features of rest tremor using a three-dimensional built-in accelerometer and robust software packages.…”
Section: Emerging Technologies In Assessing Motor Functionmentioning
confidence: 99%
“…In past studies, IMUs have shown to be both accurate and repeatable for measuring gait parameters in healthy young adults (Washabaugh et al, 2017). Additionally, publicly available datasets collected from patients with movement disorders using IMUs have been utilized to analyze gait parameters and freezing of gait episodes (O'Day et al, 2022).…”
Section: Introductionmentioning
confidence: 99%